HORMONAL PROFILE OF IRAQI BITCHES DURING VARIOUS PHYSIOLOGICAL STAGES. - Nazih Wayes Zaid (Basrah Journal of Veterinary Research)
The study was conducted to investigate the success of inducted estrus and to track the hormonal levels during the estrus cycle, pregnancy and post-parturition in dogs. Ten females, aged 2-3 years and weighted 18-22 kg, were kept in cages at the College of Veterinary Medicine-University of Baghdad. Dogs were mated and tracked till they become conceive. Then, after one month of parturition, they treated with Bromocriptine (Parlodel) a dose of (0.05mg/kg/dog) twice daily to induce estrus. Eight dogs showed estrus and mated again with the same mature dogs. Blood serum was taken once a week from cephalic vein. Follicular Stimulating Hormone (FSH), Luteinizing hormone (LH), Estrogen and Prolactin were measured by using canine Gamma counter kits. In both, normal and induced estrus periods, FSH and LH hormone levels started to elevate in proestrus and estrus phases then they declined in pregnancy months and post-parturition. Estrogen and prolactin hormones had significant differences during the second month in the other non-responsive dogs. Estrogen levels indicated that the proestrus, estrus and treatment period showed higher significant differences (P